Peran Kompensasi Terhadap Peningkatan Kinerja Karyawan Pada Perbankan Syariah Palembang - RA. Ritawati RA. Ritawati (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2015)
Compensation has big effect on motivation, performance and employee worksatisfactions. Theoretically, giving a fair compensation will increase employee’sproductivity, and finally improve the wealth of institution. Using qualitativeanalysis with open‐close interview procedures, this research finds out thatcompensation on employees in Islamic banking could improve employee’s loyaltyand productivity. It could be seen from the assessment of employee productivitydone by managers of Islamic banking in Palembang on many years under studythat had increased. Such improvement in employee productivities not only oftangible productivity manner but also intangible.Key Words: Compensation, Employee’ Performance, and Islamic Banking